Development and performance evaluation of a prototype electric hybrid powertrain system for automotive applications - Abdul Aziz, Azhar; Lim, Chon Wei (The Institution of Engineers Malaysia, 2005)

(untitled)
Researchers at Universiti Teknologi Malaysia (UTM) have developed a dedicated hybrid power plant based on the parallel configuration using a gasoline engine coupled to a high performance electric motor, specifically targeted for automotive application. The aims are to achieve even lower exhaust emissions, better fuel economy and better performance than the conventional arrangement, demonstrating an alternative solution to the conventional power plant. The engine used is a 1.3 litre spark-ignition, coupled with a 27.5 kW Nexus electric motor. The control strategy developed in conjunction with the program is to use the electric drive motor for initial acceleration and for regeneration braking energy recovery, and for reducing the peak load and transients seen by the engine. A relatively small pack of advanced lead acid batteries is use for energy storage. The design, development and evaluation exercises are fully described giving a comprehensive insight of the prototype and its capabilities.